Corporate financing dynamics: Malaysia empirical evidence - Haron, Razali; Ibrahim, Khairunisah; Mat Nor, Fauzias; Ibrahim , Izani (2012)
This study focuses on the dynamic aspect of corporate financing which is a relatively new area in the finance literature. By employing panel data, 790 of non-financial listed firms in Malaysia are examined for the period of 2000-2009. Conducted using the dynamic Partial Adjustment Model and estimated based on the Generalized Method of Moment, this study investigates the existence of target capital structure, speed of adjustment and factors affecting speed of adjustment. There are evidences of target capital structure and firms do adjust to be at their target from time to time with a considerably rapid speed of adjustment, in line with dynamic trade-off theory. Firms in Malaysia are found to be under-adjust, being below the required adjustment to be at the target within a year. Study on factors affecting speed of adjustment is a new contribution to the literature as no work has been done regarding this issue in Malaysia. This study also analyses firm-specific factors affecting speed of adjustment. There is strong evidence on the negative relationship between speed of adjustment and distance from target leverage suggesting fast adjustment if not being far from target. Firm size and profitability significantly influence speed of adjustment for firms in Malaysia.